1992
DOI: 10.1104/pp.98.1.380
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine Ammonia-Lyase from Loblolly Pine

Abstract: Phenylalanine ammonia-lyase (EC 4.3.1.5) has been purified from differentiating secondary xylem of loblolly pine (Pinus taeda L.). Native molecular weight of the enzyme was estimated to be 280,000, with a subunit molecular weight of 74,000; isoelectric point, 5.8; and Michaelis constant for i-phenylalanine, 27 micromolar. No evidence was obtained for the existence of isoforms of the enzyme, nor for negative cooperativity of substrate binding. Polyclonal antibodies were raised against the phenylalanine ammonia-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The PAL1, CCR and CAD genes were selected for this study because of their previously described importance in wood formation in other species (WHETTEN and SEDEROFF, 1992;WHETTEN and SEDEROFF, 1995;LI et al, 2006;O'MALLEY et al, 1992). For the PAL1 gene, a P. sylvestris gene sequence was available, while for the other two genes, sequences from P. taeda were utilised for primer design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PAL1, CCR and CAD genes were selected for this study because of their previously described importance in wood formation in other species (WHETTEN and SEDEROFF, 1992;WHETTEN and SEDEROFF, 1995;LI et al, 2006;O'MALLEY et al, 1992). For the PAL1 gene, a P. sylvestris gene sequence was available, while for the other two genes, sequences from P. taeda were utilised for primer design.…”
Section: Discussionmentioning
confidence: 99%
“…In Pinus taeda, a single PAL gene was identified in a xylem-specific cDNA library (WHETTEN and SEDEROFF, 1992), while in angiosperm genomes, PAL belongs to a multigene family, and it has been suggested that gymnosperm and angiosperm lignin biosynthesis pathways are highly distinct. However, in Pinus banksiana, research suggests that PAL is encoded by a multigene family (BUTLAND et al, 1998), and it has been reported recently that there are actually five PAL genes in the P. taeda genome (BAGAL et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme was partially purifi ed in a two-step procedure involving ammonium sulfate (Merck, Darmstadt) precipitation and dialysis (21,22). The enzyme extract was brought to 60 % saturation by gradual addition of solid ammonium sulfate while stirring at 4 °C.…”
Section: Partial Purifi Cation Of Palmentioning
confidence: 99%
“…Polyphenol oxidase (PPO) was assayed using the modified method of Mayer et al (1966) using 0.1 M PB (pH 6.5) and 0.01 N catechol along with enzyme extract. The phenyl alanine lyase (PAL) assay was conducted using 400 ml of 50 mM Tris-HCl (pH 8.8) and 600 ml of 1 mM Lphenylalanine along with enzyme extract as reaction mixture (Whetten & Sederoff 1992).…”
Section: Assay Of Stress-related Enzymes and Compoundsmentioning
confidence: 99%